Age at the time of hip fracture in patients with rheumatoid arthritis is 4 years greater than it was 10 years before, but is still younger than that of the general population. Issue 1 (2nd January 2020) - Arai, Katsumitsu; Suzuki, Nobuaki; Murayama, Takayuki; Kondo, Naoki; Otsuka, Hiroshi; Koizumi, Masahiro; Hosaka, Noboru; Fujikawa, Ryuta; Yanabashi, Kazuhito; Sasage, Yosuke; Yoshida, Ken; Kimura, Keishi; et al.
Abstract: Objective: To investigate the characteristics of hip fractures in patients with rheumatoid arthritis (RA). Methods: Between 2012 and 2015, 789 hip fractures were treated at our hospital. Patients with RA were checked and their characteristics were compared with data recorded 10 years before, and with the general population. Results: There were 11 patients with RA, who were all female, and the mean age was 76 ± 7.0 years. The age at the time of hip fracture was 4 years older than that recorded 10 years before (72 ± 4.5 years, p < .05), but was younger than that of the general population (84 ± 8.0 years, p < .001). The mean prednisolone dose of 2.5 ± 2.6 mg/day was lower than that recorded 10 years before (4.8 ± 2.9 mg/day, p < .05). The rate of patients treated with anti-osteoporotic medications at fracture (73%) was higher than 10 years before (42%); however, the difference was not significant. The incidence of secondary fracture was not high compared to the general population. No mortality was recorded at 1 year, and no infective complications occurred. Conclusion: The age at the time of hip fracture in RA patients is increasing, but is still younger than that of the general population.